IMPLEMENTASI MODERASI BERAGAMA DI SMP NEGERI 4 SAMPIT - Elyanti, Fahilda Nur; Rizal, Setria Utama; Anshari, Muhammad Redha (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
Religious moderation is an important key in maintaining social harmony amidst the diversity that exists in Indonesia, including in the educational environment. This article discusses the concept and implementation strategy of religious moderation at SMP Negeri 4 Sampit, Central Kalimantan. The research method used in this study is qualitative. The data sources include 4 Muslim teachers, 4 non-Muslim teachers and 1 principal. The data collection techniques used are observation, interviews and documentation. The data validation techniques used are triangulation techniques and source triangulation. While the data analysis techniques are data reduction, data presentation, and conclusions. The results of the study show that religious moderation is understood as a balanced religious attitude, namely practicing religious teachings with full confidence while respecting the differences in other people's beliefs. This concept is internalized through the values ​​of love, tolerance, and openness between religious communities. The implementation of the strategy is carried out comprehensively through classroom learning, interfaith activities, and collaboration between religious teachers to build an inclusive school environment. Dialogic approach, teacher role model, and habituation of tolerance values ​​are the main keys in forming moderate student characters. SMP Negeri 4 Sampit aims to form a young generation that is not only religious, but also tolerant and loving within the framework of diversity.